THE DERIVATIONAL AFFIXES ANALYSIS OF GAP FILL PARAGRAPH ON UNAS AT SENIOR HIGH SCHOOL - Fatih Al Fauzi (Universitas Islam Lamongan, 2018)
Affixation is the use of adding a morpheme or affix to an already existing word to create a new word to help describe its use in a sentence, and there are two types of affixes Derivational and Inflectional. Affixes can found in the various text, in newspaper, magazine and in media online text act. This research is focus on Derivational Affixes analysis on Gap Fill paragraph at UN (National Examination). Analyzing UN is one way to know the extent to which the quality of the UN that we use in the exam national system that we use in the learning system and also have an important role for the teacher and student learning as a reference and to assist student learning. While the result of the study Derivational affixes in gap fill paragraph on UN (National Examination) are –ly (8), un- (1), -ion (1), -ment (1), dis- (1). It shows that have the most frequently appear in gap fill paragraph on UN (National Examination) are suffix –ly as an adverb marker. The word of changing the part of speech that found in gap fill paragraph on UN (National Exam) are : adjective, adverb, noun and verb